"It's a Family Issue!". Issue 1 (May 2017) - Heinemann, Isabel
Abstract: In American society, as elsewhere, social change has brought about a shift from the traditional nuclear family to more diverse forms of family, fatherhood and motherhood. But the much‐cited change in family values and gender roles has not been linear – new research reveals a picture with light and dark sides.